Instilling And Shaping Religious Character In Madrasah Ibtidaiyyah - Jamilah Jamilah; Tri Sukitman; Jamilah (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2020)
This research is aimed at describing the imposing and shaping of religious character and describing the methods used in shaping religious character at Madrasa Ibtidaiyyah Tarbiyatus Shibyan Jadung Dungkek. This is a qualitative research whose data were obtained from observation, interview, and documentation. The data collected then analyzed by Miles and Huberman analysis model including four components namely data collection, data reduction, data display, and conclusion. This research resulted in findings that the imposing and shaping of personal and ritual religious character is supposed to not only involve family but also develop education partnership among family, school, and community. The methods carried out to impose and shape the character for the students are through exemplary, advice, supervision, and punishment. Religious character education must be integrated in all subject lessons taught at the Madrasah